Exploring the Potential of ChatGPT Integration in HRM for SMEs: Enhancing Productivity, Stimulating Creativity, and Promoting Sustainable Business Innovation - Doni Arie Rosandy (Politeknik Ganesha Medan, 2024)
Micro, Small, and Medium Enterprises (MSMEs) often face limitations in terms of quantity and quality of human resources. These limitations can hinder MSMEs' ability to innovate and compete in an increasingly complex market. The utilization of technology can assist MSMEs in enhancing operational efficiency. However, not all MSMEs are capable of adopting advanced technology due to resource constraints and limited technological understanding. The aim of this research is to investigate the potential and effectiveness of integrating ChatGPT into Human Resource Management Systems (HRMS) for MSMEs, with a focus on enhancing productivity, stimulating creativity, and fostering sustainable business innovation. The research method employed is a literature review with a qualitative approach and descriptive analysis. The literature review is utilized to explore relevant literature from Google Scholar for the period 2018-2024. The study findings indicate that in the continually evolving digital era, technology integration such as ChatGPT in HRMS for MSMEs holds significant potential for enhancing operational efficiency, productivity, creativity, and business innovation. Through the implementation of this strategy, MSMEs can optimize their human resource management, create significant added value, and strengthen their position in an increasingly competitive business environment.